2018
DOI: 10.1016/j.jhep.2018.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota mediates diurnal variation of acetaminophen induced acute liver injury in mice

Abstract: Acetaminophen (APAP) induced acute liver failure because of over dose is a leading public health problem. APAP-induced liver injury exhibits diurnal variation, specifically APAP causes more severe liver damage when taken at night compared with in the morning. Herein, we showed that gut microbial metabolite, 1-phenyl-1,2-propanedione is involved in the rhythmic hepatotoxicity induced by APAP, by depleting hepatic glutathione (an important antioxidant) levels. Our data suggest gut microbiota may be a potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
197
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 204 publications
(204 citation statements)
references
References 37 publications
4
197
1
2
Order By: Relevance
“…On one hand, germ‐free mice were found to be equally susceptible to APAP liver injury as conventionally housed animals . On the other hand, antibiotic‐treated mice were found to be protected from APAP hepatotoxicity, which was linked to the contribution of the bacterial metabolite 1‐phenyl‐1,2‐propanedione enhancing liver injury . However, because liver injury is the immediate and acute concern with APAP toxicity, an overlooked and unexplained observation is that APAP ALF transplant recipients have been found to have higher short‐term mortality rates than patients who have undergone transplantation for other etiologies of ALF .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, germ‐free mice were found to be equally susceptible to APAP liver injury as conventionally housed animals . On the other hand, antibiotic‐treated mice were found to be protected from APAP hepatotoxicity, which was linked to the contribution of the bacterial metabolite 1‐phenyl‐1,2‐propanedione enhancing liver injury . However, because liver injury is the immediate and acute concern with APAP toxicity, an overlooked and unexplained observation is that APAP ALF transplant recipients have been found to have higher short‐term mortality rates than patients who have undergone transplantation for other etiologies of ALF .…”
Section: Discussionmentioning
confidence: 99%
“…As has now been well established, loss of intestinal barrier function is a major contributor to various modes of liver injury and potentially other disorders, including those considered to be of neurologic origin, such as Parkinson’s disease . Importantly, although a few studies have focused on potential contributions of the gut microbiota on APAP‐induced liver injury, APAP‐induced intestinal damage has not been fully explored …”
mentioning
confidence: 99%
“…We previously found that gut bacteria–derived saturated fatty acids exerted protective effects against alcohol‐induced liver injury . Moreover, certain dicarbonyl compounds could regulate liver damage in the context of drug‐induced acute liver failure . In addition, the intestinal microbiota is the upstream modulator of systemic immunity, which plays key roles in sepsis development.…”
mentioning
confidence: 99%
“…(15) Moreover, certain dicarbonyl compounds could regulate liver damage in the context of drug-induced acute liver failure. (16) In addition, the intestinal microbiota is the upstream modulator of systemic immunity, (17,18) which plays key roles in sepsis development. Based on these findings, it is possible that the gut microbiota is a key contributor to the pathogenesis of sepsis and related liver injury.…”
mentioning
confidence: 99%
“…NAPQI can be further detoxified by glutathione (GSH). Upon GSH depletion, excess NAPQI modulates protein structures and induces mitochondrial dysfunctions, mediating hepatocyte death, dysregulation of immune responses, and liver damage . Although this pathway is well recognized, the factors mediating APAP‐associated cytotoxicity, especially in extrahepatic tissues, remain unknown.…”
mentioning
confidence: 99%